Finding “Win-Win” – China’s Arctic Policy and what it means for Canada - Adam Lajeunesse (University of Calgary, 2018)
China is a “Near Arctic State” with national interests in Arctic resources, shipping lanes, and regional governance. That was the message delivered to the world in China’s new Arctic policy. The philosophy espoused in this White Paper is one of cooperation and mutual profit – what the Chinese have dubbed “win-win” polar partnerships. These partnerships have been expanding in recent years. Tens of billions of dollars in Chinese capital has flowed into oil and gas projects in Siberia and the Russian Arctic offshore, new shipping routes are being tested, and state-owned mining companies have acquired rich mineral deposits in Greenland and – to a lesser extent – Canada. These resources, and the sea lanes that connect them, have been labelled the “Polar Silk Road,” a maritime trade and shipping route supported by Chinese infrastructure spending running through the Northwest Passage and other circumpolar channels. China’s increasingly confident posture in the North represents real opportunities – and challenges – for Canada. Managed property, Chinese money can support the decades old Canadian dream of developing the Northwest Passage as a useable sea route, decreasing shipping costs, supporting development and improving the quality of life for Arctic residents. Managed incorrectly, Chinese activity might leave the Asian power with a degree of de facto control over the Arctic, damaging Canadian sovereignty and imperiling the country’s ability to manage this increasingly important region on Canadian terms. This new White Paper is as clear a signal as can be sent that China is coming into the Arctic with long-term strategic ambitions. Canada should not fear this development, but it must be prepared for it.